Arrogance and Forgetfulness: Analyzing the Roots of Moral Degradation from a Spiritual Perspective - Tita Setiawati; Nia Qurniati Rahmani; Ida Yunengsih (Islamic Journal of Education, 2024)
The phenomenon of moral degradation has become a significant issue in contemporary society, particularly in an era marked by disruption, individualism, and hedonism. This moral decline is evident in the rise of traits such as arrogance and forgetfulness, which are seen as fundamental roots of moral negligence. These behaviors lead to various forms of deviance, including violence, misuse of technology, free sex, integrity erosion, bullying, disrespect, and corruption. Identifies arrogance and forgetfulness as the core traits driving moral degradation. Arrogance, symbolized by Satan's downfall due to pride, and forgetfulness, represented by Prophet Adam’s disobedience regarding the forbidden tree, contribute to this decline. This study explores these traits from the perspective of Islamic spirituality and their impact on social life, employing library research with a qualitative-descriptive approach. The findings suggest that arrogance involves denial of truth and belittlement of others, while forgetfulness entails neglect of life’s purpose and divine trust. If not addressed, these traits can lead to systemic moral corruption. The study recommends revitalizing spiritual education based on monotheism (tauhid) and self-reflection (muhasabah) as essential tools for combating moral degradation, with a focus on reflection and sincere repentance, particularly through practices like remembering death (dzikri maut)